Clinical and Radiological Outcomes After Revascularization of Hemorrhagic Moyamoya Disease - Kang, Kaijiang; Lu, Jingjing; Ju, Yi; Ji, Ruijun; Wang, Dandan; Shen, Yuan; Yu, Lebao; Gao, Bin; Zhang, Dong; Zhao, Xingquan (Frontiers in Neurology, 2020)
Objective- To evaluate clinical and radiological outcomes after revascularization of hemorrhagic moyamoya disease (MMD). Materials and Methods- We retrospectively collected patients with hemorrhagic MMD who received revascularization from January 2011 to June 2018 at a high-volume stroke center. Rebleeding, ischemic stroke, modified Rankin Scale (mRS) and death after revascularization were used to evaluate long-term clinical outcome. Poor neurological outcome was defined as an mRS>2. The changes of original and revascularization collaterals were used to evaluate radiological outcome. The clinical and radiological outcomes between patients with different surgical revascularization were compared. Results- A total of 312 patients (319 hemispheres) were recruited, including 133 hemispheres (41.7%) with indirect revascularization and 186 hemispheres (58.3%) with direct revascularization. In 308 hemispheres with clinical follow-up data, Postoperative rebleeding, ischemic stroke, poor neurological outcome and death occurred in 13.0% (40/308), 2.6% (8/308), 12.0% (37/308) and 6.2% (19/308) of the hemispheres respectively. The rates of postoperative rebleeding (8.5% versus 19.1%, P=0.006) and poor neurological outcome (8.5% versus 16.8%, P=0.026) were lower in hemispheres with direct revascularization than those with indirect revascularization. However, there was no statistically significant difference in the rates of postoperative ischemic stroke (1.1% versus 4.6%, P=0.129) and death (4.5% vs 8.4%, P=0.162) between the two groups. Multivariate logistic regression analysis indicated that the risk of postoperative rebleeding was higher in those with untreated aneurysms, repetitive bleeding episodes, normal perfusion status, and indirect revascularization (P<0.05). In 78 hemispheres with radiological follow-up data, the regression of moyamoya vessels, AchA, PcomA and aneurysms were present in 44.9%, 47.4%, 25.6% and 11.5% of the hemispheres respectively. The regression of original collaterals and establishment of revascularization collaterals were more significant in hemispheres with direct revascularization than those with indirect revascularization (P<0.05). Conclusion- Direct revascularization may be superior to indirect revascularization for prevention of rebleeding and poor neurological outcome in adults with hemorrhagic MMD. The risk of postoperative rebleeding was higher in those with untreated aneurysms, repetitive bleeding episodes, normal perfusion status, and indirect revascularization. The regression of original collaterals and establishment of revascularization collaterals after revascularization were more significant in hemispheres with direct revascularization than those with indirect revascularization.